The Mediating Role of Non-verbal Behaviors in the Relationship Between Interdependent Self-construal and Transformational Leadership - Nagpal, Malini; Ensari, Nurcan (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study examined the relationship between interdependent self-construal and perceptions of transformational leadership, and the mediational role of non-verbal behaviors that reflect intention to build relationship (ITBR). One hundred and forty business managers took part in a multiphase study. In phase 1, they delivered speeches while being recorded. In phase 2, their non-verbal behaviors were coded by independent coders using Laban Movement Analysis. In phase 3, different independent coders listened the participants’ speeches and rated their level of transformational leadership. Structural Equation Modeling (SEM) and bootstrapping analyses were utilized to test several mediational paths. The results supported our hypothesis that nonverbal movements, specifically light weight, free flow, indirect space and process-oriented movements, mediated the relationship between interdependent self-construal and transformational leadership. The theoretical and practical implications are discussed within the context of self-construal and leadership theories.